Functionality assessment of building a microclimate system utilising solar energy in a cold climate - Januševičius, Karolis (Strojniški vestnik, 2019)
Bringing clean and affordable energy to the market is one of the goals of sustainable development set by the United Nations. Thermal comfort is an important aspect of efficient energy use, which plays a crucial role in ensuring health and well-being in the built environment. The majority of energy in the building sector is consumed by microclimate systems that provide thermal comfort for occupants. Design strategies, such as passive and active solar and thermal mass utilisation, reduce heat demand. When aiming to optimise thermal comfort, a reasonable combination is important in order to increase the utilisation of clean renewable energy, while conserving other resources. In this paper, a method to generate design charts is proposed to assess early design options. It aids in the selection of design parameters, based on targeted seasonal thermal comfort as a function of a complex microclimate system. In order to explore the interaction between design variables, a TRNSYS simulation model was used. An analysis of comfort conditions (based on the EN ISO 7730 method) in building spaces was performed to assess functionality. The simulation model accounted for the thermal constant in building spaces, solar utilisation and gain through glass surfaces, solar collectors and active accumulation, energy transportation, and distribution efficiency. The presented case study results showed that the lack of space heating capacity (3/4 of the calculated quantity) could be compensated for by thermal mass and a solar thermal collector without compromising thermal comfort (the Percentage of people dissatisfied (PPD) was below 10%). The highest solar fraction (36%) was reached with the lowest fractions of space heating capacity (1/2 of the calculated quantity), due to increased demands, but this design option did not satisfy the thermal comfort conditions (PPD>17%).
Keywords: early design tool; orodje za zgodnje faze načrtovanja; solar thermal; sončno ogrevanje; thermal comfort; toplotno ugodje